ICT in Education Policy, Ministry of Education and Youth, Jamaica 2022 - Jamaica. Ministry of Education and Youth (Ministry of Education and Youth, Jamaica, 2022)
This policy will provide the framework for the appropriate provisions, use and management of ICTs in Education. It will apply to all institutions providing educational programmes and services that are consistent with the standards for quality education. This policy gives details for achieving the following goals: 1) Transforming the teaching and learning process, 2) Learning opportunities for all, 3) Efficient management and administration of the education system, and 4) Promoting the development of ICT innovations.